Analisis Hubungan Upah Minimum Regional dan IPM terhadap Tingkat Partisipasi Angkatan Kerja di Kabupaten Mandailing Natal - Nursalamah, Nursalamah (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of the Regional Minimum Wage (RMW) and the Human Development Index (HDI) on the Labor Force Participation Rate (LFPR) in Mandailing Natal Regency. The research is motivated by employment issues, where increases in RMW and improvements in HDI do not necessarily correspond with a higher labor force participation rate. A quantitative research approach was employed using secondary data obtained from the Central Bureau of Statistics (BPS) for the 2018–2022 period. The analytical method used is multiple linear regression, supported by a series of classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, to ensure model validity and reliability. The results indicate that: (1) the Regional Minimum Wage (RMW) has a significant negative effect on the Labor Force Participation Rate (LFPR); (2) the Human Development Index (HDI) has no significant effect on LFPR; and (3) RMW and HDI simultaneously have a significant influence on LFPR, with a combined contribution of 81.8%. These findings suggest that the RMW is a more dominant factor in determining labor force participation compared to HDI. The study concludes that wage adjustments should be balanced with the labor market’s absorption capacity. Furthermore, improvements in human resource quality must be accompanied by efforts to expand employment opportunities to ensure sustainable labor participation and inclusive economic growth.